Effect of activation conditions and iron loading content on the catalytic cracking of toluene by biochar. (15th May 2022) - Liu, Haolin; Ye, Chao; Xu, Yousheng; Wang, Qisong
Abstract: Biochar (BC) is a catalyst carrier with a porous structure and low production cost. Herein, a Fe-loaded BC catalyst was prepared by impregnation and calcination, and use toluene to determine the removal efficiency of the catalyst. When the Fe impregnation solution mass fraction was 4%, the removal efficiency for the Fe-loaded BC catalyst was 94.1%. The amount of H2 produced by toluene catalysis is 963.22 ml, which is about three times the total amount of H2 produced by toluene self-pyrolysis and catalyst self-gasification. The effects of steam activation conditions and Fe impregnation mass fraction on the microstructure of BC were studied. The results show that the activation temperature and time can increase the BET surface area. A high concentration of steam volume and impregnation solution decreases the BET surface area. The characterizations of the catalyst before and after the toluene removal experiment shows that C–O bond plays a vital role in the removal process and micropores of BC preferentially adsorb toluene. The adsorption mechanism on BC mainly depends on n–π interaction and pore filling. The electrostatic attraction and π–π interaction on Fe-loaded BC were enhanced. Loading treatment introduces lattice oxygen and leads to increased oxygen vacancies. Highlights: Catalytic cracking of toluene with Fe-loaded biochar increases hydrogen production. Fe loading treatment can improve the removal efficiency of toluene from biochar. Biochar relies on pore filling and n–π to remove toluene. Fe loading treatment can increase oxygen vacancies and hydroxyl groups.